Notoginsenoside R1 for Organs Ischemia/Reperfusion Injury: A Preclinical Systematic Review - Tong, Qiang; Zhu, Peng-chong; Zhuang, Zhuang; Deng, Li-hui; Wang, Zi-hao; Zeng, Hua; Zheng, Guo-qing; Wang, Yan (Frontiers in Pharmacology, 2019)
Abstract Notoginsenoside R1 (NGR1) exerts pharmacological actions for a variety of diseases, including myocardial infarction (MI), ischemic stroke, acute kidney injury (AKI) and intestinal injury. Here, we conduct a preclinical systematic review of NGR1 for ischemia reperfusion (I/R) injury. Eight databases were searched from their inception to February 23rd, 2019. Review Manager 5.3 (RevMan 5.3) was applied for data analysis. CAMARADES 10-item checklist and cell 10-item checklist were used to evaluate the methodological quality. Twenty-five studies with 304 animals and 124 cells were selected. The risk of bias scores of animal studies ranged from 3 to 8, whereas the cell studies ranged from 3 to 5. NGR1 decreasing myocardial infarct (MI) size in myocardial I/R injury, decreasing cerebral infarction volume and neurologic deficit score in cerebral I/R injury, decreasing serum creatinine in renal I/R injury and decreasing Park/Chiu score in intestinal I/R injury compared with controls (all P<0.05 or P<0.01). The possible mechanisms of NGR1 for I/R injuries exerted multiple organs protection, mainly through antioxidant, anti-apoptosis, anti-inflammatory, promoting angiogenesis and improving energy metabolism. The findings showed that NGR1 possess organs protection after I/R injury, and potentially become a novel drug for ischemic diseases. Further clinical trials are needed.